Awakening to equality a young white pastor at the dawn of civil rights - Lutze, Karl E.; ebrary, Inc. (Columbia : University of Missouri Press, 2006)
"In 1945, Karl Lutze was a young white pastor assigned to an African American church in Muskogee, Oklahoma. His experiences ministering to Black congregations there and, later, in Tulsa provide a unique perspective on the early civil rights movement in Oklahoma and within the Missouri Synod of the Lutheran Church"--Provided by publisher.
Includes index.
Electronic reproduction.
Keywords: Lutze, Karl E; Lutheran Church--Missouri Synod -- Biography; African American churches -- Oklahoma -- History -- 20th century; African Americans -- Civil rights -- Oklahoma -- History -- 20th century; Civil rights movements -- Oklahoma -- History -- 20th century; Lutheran Church -- Oklahoma -- Clergy -- Biography; Whites -- Oklahoma -- Biography; Muskogee (Okla.) -- Race relations; Oklahoma -- Race relations; Tulsa (Okla.) -- Race relations; Electronic books